Pengaruh Manajemen Dapur Berkelanjutan terhadap Limbah Makanan Program Makan Bergizi Gratis (MBG) - Eryd Saputra; Frangky Silitonga; Tirta Mulyadi; Heri Nuryanto; Hanifah Malya Fakhriani (CV. ITTC INDONESIA, 2026)
The Free Nutritional Meal Program (MBG) is designed to improve the nutritional quality of students by providing nutritious food in the school environment. Kitchen operations are a crucial factor in determining the program's success because they are related to food quality, efficient use of food ingredients, and food waste management. This study aims to analyze the condition of kitchen management, the implementation of sustainable kitchen management, and food waste in the operations of the Free Nutritional Meal Program. The study used a quantitative approach with a survey method of the MBG kitchen workforce in Batam City. This study used a quantitative survey method of 65 kitchen operational workers of the Free Nutritional Meal Program (MBG) in Batam City using a total sampling technique. Data analysis was conducted using descriptive statistics and multiple linear regression assisted by SPSS. The results of the study indicate that kitchen management and sustainable kitchen management are in the good category. Practices of production planning, raw material management, food safety, and sanitation have been implemented quite effectively in supporting kitchen operations. Food waste is still found at a moderate level, indicating food waste and food waste during the production process. The research findings indicate that strengthening kitchen management and implementing sustainability principles can support operational efficiency and reduce food waste. More planned and sustainable kitchen management is an important part of supporting the success of the Free Nutritious Meal Program.